Análise dos aspectos econômicos da avicultura mundial, brasileira e das condições socioprodutivas da agroindústria na região oeste de Santa Catarina - Rachor, Enrique (2020)
International trade and the organization of food agroindustries, mainly in the broiler chicken value chain, has undergone significant changes. This triggers a massive reaction in all sectors, before, inside and after gate. Currently, Brazil is the third largest chicken meat producer, fourth consumer and the largest exporter one, where Santa Catarina stands out as the state with second largest production and export in the country, having in its territory a range of agroindustries aimed at the foreign market. The objective was to analyze socio-economic aspects of poultry meat agribusiness in western Santa Catarina region, in national and global market. With that, determine similarities between countries through a cluster analysis by the variables production, export, import and domestic consumption, 2019, defining the Market Share of those with the greatest representativeness, allowing, through the calculation of the geometric growth rate, to make predictions of short (5 years) and medium (10 years) terms future scenarios. This analysis logic was repeating for Brazilian states and Santa Catarina municipalities too. In addition, with a field survey, it was possible to identify the profile of broiler producers and the contribution of integrated poultry to generate employment and income in the western region of Santa Catarina. As a result, the production variable was the one that most contributed to clustering of countries / states / municipalities, showing, in the medium-term world scenario, a displacement of main producing and exporting countries to Eastern Europe, Eurasia and the Middle East, with countries in Asia being the largest importers of chicken meat. USA and Brazil hegemony will not threatened, given the distancing of other countries by quantity produced. In Brazil, Paraná state will continue being the largest producer and exporter and Santa Catarina will significantly increase its exports, with municipalities of western Santa Catarina contributing even more to this scenario. Also, research has shown that small producers are the base of global value chain in the west of Santa Catarina, specifically in the micro-region of Chapecó, with advanced age (49 years average), high representation of their income from poultry production (55% average), well-equipped aviaries, excellent batches produced performance indexes, with polyculture as a means of subsistence on their property, since the financing does not allow them to survive only with broiler monoculture. Finally, it concerns the producer feeling valued by the agroindustry, recognizes the importance of it for improving his income and for technical assistance, with well-equipped aviaries. However, the scenario of poultry farming in the region could be a problem, because children who will stay on the rural property have no interest in crop continuation, replacing it by corn and soybean mainly.